2020
DOI: 10.1177/1468087419896647
|View full text |Cite
|
Sign up to set email alerts
|

The effects of material and structure of main bearing caps on crankshaft lubrication of diesel engine

Abstract: The elastic deformation of the crankshaft and engine block has important effects on lubrication performance of main bearings of the diesel engine. But the effect of main bearing caps was rarely analyzed. The purpose of this article is to analyze and compare the tribological performances of main bearings of a 20-V medium-speed diesel engine with different materials and structures of main bearing caps. A coupled multi-elastic body and elasto-hydrodynamic model is established for a 20-V medium-speed diesel engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Both are highly undesirable as the presence of lubricants in combustion chamber has a negative impact on the output emissions while the unburnt fuel and exhaust gases in the oil sump contaminate the lubricants and therefore greatly affects its performance. 22 The presence of lubricant in combustion chamber would produce a significant increase in the particles emitted with sizes larger than 50 nm as reported by Amirante et al 24 In addition, it has been reported 25 that the lubrication performance in terms of the distribution of oil film pressure, thickness and bearing thermal loads has been improved when the main bearing cap is made of iron instead of steel.…”
Section: Optical Engine Designmentioning
confidence: 91%
“…Both are highly undesirable as the presence of lubricants in combustion chamber has a negative impact on the output emissions while the unburnt fuel and exhaust gases in the oil sump contaminate the lubricants and therefore greatly affects its performance. 22 The presence of lubricant in combustion chamber would produce a significant increase in the particles emitted with sizes larger than 50 nm as reported by Amirante et al 24 In addition, it has been reported 25 that the lubrication performance in terms of the distribution of oil film pressure, thickness and bearing thermal loads has been improved when the main bearing cap is made of iron instead of steel.…”
Section: Optical Engine Designmentioning
confidence: 91%
“…17 However, local phenomena studies for lubricants include friction, shear, cavitation, and heat transfer. Most of these studies analyse the problem with a standalone model to minimize the uncertainties, [18][19][20][21] as in experimental procedures with tribometers and rheometers.…”
Section: Introduction and Scopementioning
confidence: 99%
“…Zhang et al (2020) established the hydrodynamic lubrication model of the main bearing and analyzed the influence of the balance rate, bearing width and radial clearance on the oil film and friction loss. Wu et al (2021) analyzed the influence of the material and structure of the bearing cover on the bearing oil film pressure, film thickness and thermal load. Gao et al (2019) established a lubrication model based on the Reynolds equation and studied the effects of axial movement, crankshaft deformation and surface roughness on the lubrication characteristics of the main bearing.…”
Section: Introductionmentioning
confidence: 99%